2021
DOI: 10.1007/jhep01(2021)072
|View full text |Cite
|
Sign up to set email alerts
|

Wilson-’t Hooft lines as transfer matrices

Abstract: We establish a correspondence between a class of Wilson-’t Hooft lines in four-dimensional $$ \mathcal{N} $$ N = 2 supersymmetric gauge theories described by circular quivers and transfer matrices constructed from dynamical L-operators for trigonometric quantum integrable systems. We compute the vacuum expectation values of the Wilson-’t Hooft lines in a twisted product space S1 × ϵ ℝ2 × ℝ by supersymmetric localization and show that they are equal to the Wigner transforms of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Many of the phenomena that are expected to constitute this web of dualities are yet to be uncovered, but their specializations to the case of gl(m|0) = gl(m) are known and have been studied in recent years. Besides the Bethe/gauge correspondence already described, the structures of rational gl(m) spin chains (and their trigonometric and elliptic generalizations) have appeared in quantization of the Seiberg-Witten geometries of fourdimensional N = 2 supersymmetric gauge theories [4][5][6], the action of surface and line defects on supersymmetric indices of four-dimensional supersymmetric gauge theories [7][8][9][10][11][12], quantization of the Coulomb branches of three-dimensional N = 4 supersymmetric gauge theories [13,14], and correlation functions of local operators on interfaces in fourdimensional N = 4 super Yang-Mills theory [15], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the phenomena that are expected to constitute this web of dualities are yet to be uncovered, but their specializations to the case of gl(m|0) = gl(m) are known and have been studied in recent years. Besides the Bethe/gauge correspondence already described, the structures of rational gl(m) spin chains (and their trigonometric and elliptic generalizations) have appeared in quantization of the Seiberg-Witten geometries of fourdimensional N = 2 supersymmetric gauge theories [4][5][6], the action of surface and line defects on supersymmetric indices of four-dimensional supersymmetric gauge theories [7][8][9][10][11][12], quantization of the Coulomb branches of three-dimensional N = 4 supersymmetric gauge theories [13,14], and correlation functions of local operators on interfaces in fourdimensional N = 4 super Yang-Mills theory [15], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we will see that the commutativity of elliptic Ruijsenaars operators is rephrased as the absence of wall-crossing phenomena (η-independence) of elliptic genera for the monopole bubbling effects. Recently the author of [33] observed that the localization formula [1] of 't Hooft loop operators with particular charges in 4d N = 2 * gauge theory agrees with a trigonometric limit of type-A elliptic Ruijsenaars operators [34]. Since the KK modes along the T 2 -direction give an elliptic deformation of the localization formula of the 't Hooft loops, we expect the deformation quantization of 't Hooft surface operator itself agrees with elliptic Ruisenaars operators.…”
Section: Deformation Quantization and Elliptic Ruijsenaars Operatorsmentioning
confidence: 78%
“…In Section 5, we found that the deformation quantization of 't Hooft surface operators in 5d N = 1 * gauge theory agrees with the type-A elliptic Ruijsenaars operators. Although the integrable structure appears in the 't Hooft surface operators is not manifest in the supersymmetric gauge theory, by using dualities in string theory, the brane configuration for 't Hooft operators without the monopole bubbling effect is interpreted as defects in fourdimensional Chern-Simons theory, where the quantum integrable structure naturally appear [33].…”
Section: Discussionmentioning
confidence: 99%
“…Before this work, localization for 't Hooft operators, especially with monopole screening, had been done only for SU(N ) and U(N ) gauge groups; consequently applications such as [38,[44][45][46][47][48][49] and section 8.2 of [39] had been limited to these groups. Our results here should be useful when extending these applications to SO(N ) and USp(N ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%